Phaleria macrocarpa Fruit Extract Inhibits NF-ĸB Activation and Apoptosis Induction on HeLa Cells - Meirizky Zulharini S.; Amalia Miranda; Lina Permatasari; Hilyatul Fadliyah; Riris Istighfari Jenie (Indonesian Society for Cancer Chemoprevention, 2017)
NF-κB is a transcription factor and if activated, it induces apoptosis inhibition. Phalerin from Phaleria macrocarpa fruits expected to inhibit NF-κB activation. This research is to investigate anticancer mechanism of Phaleria macrocarpa fruits extracts (EBMD) in NF-κB pathway. Molecular docking assay was performed to determine phalerin affinity to IKK. Cytotoxic activity was observed by MTT assay. Double staining was performed to determine the apoptotic cells. Docking score of phalerin to IKK is -60. The IC50 value of EBMD is 629 μg/mL. Apoptosis profile shows (shown that) many cells undergoing apoptosis after treatment. Thus, EBMD potentially inhibits activation of NF-κB pathway and triggers apoptosis on HeLa cells.Keywords : NF-κB, Phaleria macrocarpa, sel HeLa, Bcl-2, IKK, molecular docking